The Women's Recovery Group for Individuals with Co-Occurring Substance Use and Eating Disorders: Feasibility and Satisfaction in a Residential Eating Disorders Program. Issue 4 (1st October 2020) - Sugarman, Dawn E.; Meyer, Laurel E.; Reilly, Meghan E.; King, Brittany R.; Dechant, Esther; Weigel, Thomas; Tarbox, Patricia; Greenfield, Shelly F.
ABSTRACT: Despite the high rate of co-occurring eating disorders (EDs) and substance use disorders (SUDs) in women, there is a lack of integrated treatment. This study implemented the Women's Recovery Group (WRG), a gender-specific group therapy for women with SUDs, in an ED residential treatment program to assess the feasibility and satisfaction of the WRG for women with co-occurring SUDs and EDs. Women (N = 24) were enrolled in the study if they were aged 18 years or older and engaged in the WRG as part of their treatment. Patient and therapist satisfaction with the WRG were assessed post-treatment, and craving to use substances was measured at enrollment and post-treatment. Participants reported moderate satisfaction with the WRG, and therapists reported above average satisfaction with the WRG. Craving to use substances in the environment in which one previously used significantly decreased from enrollment to post-treatment. In its current form, the WRG was feasible to implement in ED residential treatment. Participants indicated that they would have liked more information on co-occurring EDs, self-image/self-esteem, shame and guilt, and maintaining sobriety at college. These results support the need for modifications to the WRG to better integrate treatment for women with co-occurring EDs and SUDs.